Packing Activated Carbons into Dense Graphene Network by Capillarity for High Volumetric Performance Supercapacitors. Issue 14 (8th May 2019) - Li, Pei; Li, Huan; Han, Daliang; Shang, Tongxin; Deng, Yaqian; Tao, Ying; Lv, Wei; Yang, Quan‐Hong
Abstract: Supercapacitors are increasingly in demand among energy storage devices. Due to their abundant porosity and low cost, activated carbons are the most promising electrode materials and have been commercialized in supercapacitors for many years. However, their low packing density leads to an unsatisfactory volumetric performance, which is a big obstacle for their practical use where a high volumetric energy density is necessary. Inspired by the dense structure of irregular pomegranate grains, a simple yet effective approach to pack activated carbons into a compact graphene network with graphene as the "peels" is reported here. The capillary shrinkage of the graphene network sharply reduces the voids between the activated carbon particles through the microcosmic rearrangement while retaining their inner porosity. As a result, the electrode density increases from 0.41 to 0.76 g cm −3 . When used as additive‐free electrodes for supercapacitors in an ionic liquid electrolyte, this porous yet dense electrode delivers a volumetric capacitance of up to 138 F cm −3, achieving high gravimetric and volumetric energy densities of 101 Wh kg −1 and 77 Wh L −1, respectively. Such a graphene‐assisted densification strategy can be extended to the densification of other carbon or noncarbon particles for energy devices requiring a high volumetric performance. Abstract : Inspired by the dense structure of irregular pomegranate grains, a densification strategy of activated carbons (ACs) is proposed by packing them into a compact graphene network with graphene as the "peels." The capillary shrinkage of the graphene network sharply reduces the voids between AC particles while retaining their inner porosity. It shows great promise for high volumetric performance supercapacitors.